We want but we can’t: measuring EFL translation majors’ intention to use ChatGPT in their translation practice - Xiaobin Ren (Humanities & Social Sciences Communications)
Abstract This study integrated technology acceptance model, theory of planned behaviour, and self-determination theory to explore translation majors’ intentions to use ChatGPT in their translation practice. Employing a quantitative research design, the study collected data from 385 English as a foreign language (EFL) translation majors across various universities in China. Analysis revealed that perceived usefulness significantly influenced students’ intentions, overshadowing perceived ease of use due to access constraints in China. Findings indicate that both controlled and autonomous motivations, along with subjective norms and attitudes, robustly shape intentions to use ChatGPT. This study challenged the conventional focus of technology acceptance model on perceived ease of use and modified the traditional theory of planned behaviour by excluding perceived behavioural control. These findings underscore the critical role of motivational and social factors in the adoption of AI tools in translation learning. The results highlight the need for tailored pedagogical approaches that integrate more accessible AI platforms, and accommodate both external motivations and intrinsic interests.